Effect of Soil Texture on Remediation of Hydrocarbons-Contaminated Soil at El-Minia District, Upper Egypt. (5th July 2012) - Abdel-Moghny, Th.; Mohamed, Ramadan S. A.; El-Sayed, E.; Mohammed Aly, Shoukry; Snousy, Moustafa Gamal
Abstract : Soils polluted by waste lubricant oils may affect the hydrosphere compromising the quality of drinking water resources and threatening the aquatic ecosystems. The objective of this study focused to remove waste-lubricant oils from different polluted sites in El-Minia governorate. In this respect some samples were collected from four different industrial sites and identified as sand, loamy sand, clay loam and loam. Then the field conditions were simulates using two experimental models packed with contaminated soil. The remediation processes carried out in both models using surfactant enhanced by air injection then by water washing. The parameters such as soil type, soil heterogeneity, time and washing process was investigated. The results indicated that the high efficiency of oil removal is obtained from sand where the clay loam gives the worst results. The results also reveal that, the high flushing and washing duration time can be attributed to the high percentage of mud in some sites over other sites. This means that the performance of surfactant flushing/water washing can be adversely affected by geologic heterogeneity. Finally, it's suitable to use pressurized liquid technologies in heterogeneous media, but cleanup times will be longer and more difficult than for the other similar homogeneous media.